One Way Video Interviewing As A Method to Augment the Residency Application [5C]. (May 2018) - Breitkopf, Daniel; Hopkins, Matthew R.; Camp, Christopher L.; Occhino, John A.; Weaver, Amy; Turner, Norman S.
Abstract : INTRODUCTION: Despite the increase in residency applications, little change in the information available for review prior to a face-to-face interview has occurred. Asynchronous or one way video interviews (OWVI) may offer a way to collect additional data on applicants. Our objective was to assess the feasibility and acceptability of OWVI and to correlate OWVI performance with in-person interview scores. METHODS: Characteristics of successful residents were identified and OWVI questions were developed using medical student volunteers. Candidates who presented for in-person interviews during the 2016-17 season for OB/GYN (n= 45) and Orthopedic Surgery (n=98) were invited to participate in OWVI with 3 questions and a maximum of 3 minutes per question. Videos were reviewed and scored independently by 2 reviewers from the respective departments using a standardized 5-point scale. RESULTS: Forty-six (47%) Orthopedic and eleven (24%) OB/GYN applicants completed OWVI. The interviewer's scores of OWVI were within one point of one another 84% of the time. High OWVI scores were correlated with higher in-person interview scores (r=0.26) and higher rank list placement (r=0.33). Sixty-two percent of the applicants were satisfied with the OWVI process. Most respondents wanted additional OWVI questions that would allow them to explain why they wanted to apply to a particular program. CONCLUSION: Asynchronous interviews enabled reviewers to differentiate applicants and their scores correlated with rank list placement and in person interview scores. The process was viewed by participants as a way to humanize their application and this may have potential to help screen applicants for residency.